Study of the Features of Disorders of the Sympathetic-Adrenal System and Immune Status in the Familial Hypercholesterolemia - Muminjanovich, Vakhabov Bahrom; Axmedovich, Hujamberdiev Mamazoir; Abduraufovich, Isakov Abdurashid (European Journal of Life Safety and Stability (2660-9630), 2022)
Presented the violations of the sympathetic adrenal system and cytokine status in patients with coronary heart disease in the family hypercholesterolemia. 144 men and women at the age of 18 to 65 years, with an average age 43,8 ±7,2 years and 15 practically healthy persons aged 20 to 50 years, with an average age 41,4 ±3,5 of the. Clinical, instrumental and special research methods were carried out. It was revealed that in the art of hypercholesterinemia, the pronounced changes of sympathetic adrenal system and cytokine status, which are more pronounced extent in patients with family hypercholesterolemia with clinical signs of CHD.